An examination of the importance of air-sea exchange in mercury cycling in the Gulf of Maine - Mason, Robert P.; Inman, Hannah M.; Smith, Sophia K.; Taylor, Vivien F. (Frontiers in Environmental Chemistry, 2025)
Mercury (Hg), primarily as methylmercury (MeHg), is a neurotoxin that biomagnifies up marine food chains, causing a health risk to humans and wildlife that consume fish. Coastal waters, such as the Gulf of Maine (GoM) are major fishing grounds, and understanding the cycling of Hg and MeHg in these ecosystems is important but understudied. Anthropogenic activity and climate change has increased temperature and altered atmospheric and terrestrial inputs of Hg and other constituents, such as dissolved organic carbon (DOC), which have further modified the aquatic transformations of Hg species within the GoM. Our study examined their impact on the overall fate and transport of Hg, and in particular the air-sea exchange of Hg, and the net formation of MeHg in the GoM. High resolution measurements of dissolved gaseous Hg (DGHg) were collected on two cruises in the GoM and the historically Hg-contaminated Penobscot River in April and August 2023 to help examine these fluxes. DGHg concentrations showed distinct seasonal trends and %DGHg was higher in the GoM even though unfiltered total Hg (HgT) concentrations were higher in the estuary. The role of DOC and other parameters in moderating surface DGHg and flux is discussed as well as how the levels of Hg and DGHg have changed since prior investigations more than a decade ago. Furthermore, the relative importance of gas exchange compared to other sinks (water flow offshore and sedimentation) was examined using water column measurements from four cruises, and a mass balance model developed for HgT and MeHg for the GoM. We used the additional information collected throughout the water column for HgT and MeHg, and correlations between variables to constrain the MeHg budget and discuss the importance of external versus internal sources and sinks for MeHg in the GoM, highlighting the importance of in situ methylation in this ecosystem. Overall, external inputs of MeHg are not the primary driver of water column MeHg concentrations, although further study is needed to confirm this conclusion.